The impact of international macro environment factors on the internationalization of Polish enterprises - Drabik, Ireneusz (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: It is commonly noted that the environment of enterprises changed substantially at the turn of the 20th and 21st centuries. The environment basic and characteristic features are changeability and complexity, i.e. turbulence. It is justified to distinguish the enterprise international macro environment as a separate category. Many different ways of understanding this category and of classifying its structural elements can be found in the literature. Aim: The theoretical aim of the article is to characterize the essence and structural elements of the international macro environment of enterprises. The practical aim is to assess the impact of individual elements of the international macro environment on the internationalization of business activity in the opinion of the Polish manufacturing companies covered by the survey. The article makes use of a critical analysis of the literature on international management and draws on the results of own surveys conducted among Polish enterprises. Results: The analysis and monitoring of changes taking place in the international macro environment are of key significance for the strategy of the enterprise internationalization regardless of the stage or intensity of the internationalization process. The influence of international macro environment factors is an important aspect that decides whether a given venture undertaken by the enterprise on foreign markets will be a success. As a result of own studies, the impact of individual types of international macro environment factors on the internationalization of Polish enterprises was determined. Attention is drawn to the dominant role of factors of the technological environment.